Modeling and Control Design for an Autonomous Underwater Vehicle Based on Atlantic Salmon Fish - Shubham Singh; Saood Ahmad; Syed Muhammad Amrr; Saleem Anwar Khan; Nazrul Islam; Abdullatif Abdulhadi Gari; Abdullah A. Algethami (IEEE Access, 2022)
Biologically inspired autonomous underwater vehicles (AUVs) or biomimetic AUVs are made to replicate the structural and physiological features of aquatic species. Thus, incorporation of its design in AUV modelling provides higher efficiency at low speeds and improves maneuverability and controllability. This paper develops a biomimetic AUV design based on structural parameters and physiology of an adult Atlantic Salmon fish and proposes a robust control scheme for propelling the fins. For the biomimetic model design of AUV, a 3D CAD model is developed using the actual parameters of Atlantic Salmon fish. The hydrodynamic analysis is performed to calculate the effect of different angles of fin orientations on the value of drag and lift coefficients. Further, kinematic analysis of the tail propulsion system is carried out using the Denavit Hartenberg convention in the MATLAB®. Based on the obtained modeling parameters of AUV, a robust sliding mode controller is proposed for tracking the desired tail propulsion response using a DC motor under model uncertainties and disturbances. Moreover, the closed-loop asymptotic stability is also guaranteed through Lyapunov theory, which ensures the convergence of system states to the desired angular movement. Lastly, the proposed algorithm is validated using simulation results with comparative performance analysis to illustrate its efficacy.